Paradigm and Operational Efficiency Strategies of Local Products: A Case Study of Songket Peci Production in Batu Bara Regency - Fikahan Melda; Dea Novika Natama Harahap; Rosnani Siregar (TATHO: International Journal of Islamic Thought and Sciences, 2026)
This study aims to describe the paradigm and strategies of production and operational efficiency in Micro, Small, and Medium Enterprises (MSMEs) of Songket Peci in Batu Bara Regency. The research method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and MSME documentation. The research results show that the songket peci production process is still carried out manually, relying on traditional skills, so the production time is relatively long. In addition, operational efficiency is not yet optimal due to limitations in equipment, time management, as well as the management of raw materials and labor. Nevertheless, the quality of the products produced has high aesthetic value and competitiveness at the local level. This study’s contribution emphasizes the importance of paradigms and strategies for production effectiveness of local wisdom products that are holistic, accommodative, and contextual.